THE RELATIONSHIP OF NUTRITIONAL STATUS AND BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS AT KARUNIA KASIH HOSPITAL YEAR 2023 - Ratnasari, Septi Ika; Widyastuti, Wiwin (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Nutritional status is a condition of the body caused by a balance between nutritional intake and needs. Breast milk (ASI) is the best nutrition and has been proven to be beneficial for the baby's life. The mother's nutritional status during lactation affecting the success of breastfeeding, malnutrition mothers are at risk of not being able to breastfeed successfully compared to well-nutrition mothers. This will negatively affect the mother's ability to produce breast milk. This situation can indicate nutritional adequacy when entering the lactation phase. Poor nutritional status of the mother and insufficient consumption of nutrients will cause the mother to become thin and unproductive in producing breast milk. Research Objective: To determine the relationship between nutritional status, parity and number of children with breast milk production in postpartum mothers. Research Method: This research used a cross sectional approach design with a sample of 1088 people. Data techniques include univariate analysis using frequency distribution and bivariate analysis using statistical calculations from the SPSS program. Research Results: The results of this study show that there is a relationship between nutritional status and breast milk production in postpartum mothers, which is (0.006) < α (0.050), indicating that nutritional status influences breast milk production, there is a relationship between parity and breast milk production in postpartum mothers with (0.020 ) < α (0.050) indicates that parity influences breast milk production, and there is a relationship between the number of children and breast milk prodution, namely (0.030) < α (0.050) indicates that the number of children influences breast milk production in postpartum mothers. Conclusions and Suggestions: there is a relationship between nutritional status, parity and number of children with breast milk production in postpartum mothers. It is recommended, to pay more attention about nutrition starting from pregnancy, so that nutrition will also be fulfilled when breastfeeding.